Sex dan masalahnya oleh W.A.R Thomson ; alih bahasa, I. Andri Hartono ; editor, Makmuri Muchlas - Thomson, W.A.R; Hartono, I. Andri; Muchlas, Makmuri (Yayasan Essentia Medica, 1981)
112 hlm ilus 22 cm